Pastured Poultry Production in the United States: Strategies to Balance System Sustainability and Environmental Impact - Rothrock, Michael J.; Gibson, Kristen E.; Micciche, Andrew C.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2019)
Nutrient and pathogen pollution are the leading causes of water quality impairment in lakes, reservoirs, and rivers in the United States. Dissemination of these contaminants can result in eutrophication of freshwater resources and pose a risk to public health through recreational contact and degradation of waters used as drinking water sources. Agricultural production practices, both crop and animal, have been identified as sources of excess nutrients and microbial pathogens contributing to freshwater pollution. In the U.S., commercial meat poultry production has been targeted as a source of both excess nutrients, especially phosphorus, and fecal indicator bacteria (FIB) in regional watersheds. Recently, there has been an increase in pastured poultry operations where chickens have access to fresh pasture on a daily basis. However, few studies have explored the environmental sustainability of these types of poultry production systems. In the case of pastured poultry systems in close proximity to watersheds, there is a need to better understand potential environmental impacts in order to implement sustainable and cost-effective practices. The identification of such environmental and economic benefits would complement the mission and objectives of farmers using pastured poultry production systems and may add more value to their product. This review will focus on potential mitigation strategies to enhance environmental sustainability and provide economic benefit to small scale pastured poultry operations.